A Hierarchical Programmable Mechanical Metamaterial Unit Cell Showing Metastable Shape Memory. Issue 11 (20th September 2018) - Berwind, Matthew F.; Kamas, Alec; Eberl, Christoph
Abstract : Hierarchically structuring materials open the door to a wide range of unexpected and uniquely designed properties. This work presents a novel mechanical metamaterial unit cell with strain‐dependent solid–solid phase changes resultant from hierarchically structured "mechanisms" built into an auxetic unit cell, and further presents a realization of this kind. The interaction of auxetic structure and mechanism allows stable or metastable elastic energy states to be reached as a result of mechanical deformation. The result is a principally elastic analog to a shape memory material with a functional dependency on its negative Poisson's ratio. Prototypes are additively manufactured using direct laser writing, and are subsequently subjected to uniaxial compression with a customized micromechanical test set up. Experimental results depict reversible states initially triggered by deformation; the unit cell is a building block for a programmable material with a nonlinear "if… then…" relationship. Implementing interior mechanisms as a hierarchical level unlocks new directions for mechanical metamaterials research, and the authors see potential impacts or applications in multi‐scale modeling, medicine, micro‐actuation and ‐gripping, programmable matter/materials. Abstract : The work presented herein depicts an auxetic metamaterial unit cell displaying a time‐dependent deformation behavior analogous to conventional shape memory materials, but achieves this through the structurally hierarchical embedding of a "mechanism". This proof‐of‐concept paper is a step in the direction of programmable materials, which are materials with reversible, functionalized properties triggered by external stimuli such as a force.